Kali Linux web penetration testing cookbook : identify, exploit, and prevent web application vulnerabilities with Kali Linux 2018.x /: identify, exploit, and prevent web application vulnerabilities with Kali Linux 2018.x. (2018) - Najera-Gutierrez, Gilberto
No abstract available